Antiepileptic drug nonadherence predicts pediatric epilepsy seizure outcomes - Modi, Avani C. (Neurology, 2014)
OBJECTIVE: The aim of the study was to determine sociodemographic, biological epilepsy-specific, and adherence predictors of long-term pediatric seizure outcomes. METHODS: This study is a prospective, longitudinal, observational study of antiepileptic drug (AED) adherence and seizure outcomes in children with newly diagnosed epilepsy. Patients were recruited from April 2006 to March 2009 and followed for 2 years. Objective, electronic monitors were used to assess AED adherence. Medical chart reviews assessed medical variables and seizure outcomes. RESULTS: Participants (n = 109) were 7.3 ± 2.9 years of age, and 62% male. Four adherence trajectory groups were identified: severe early nonadherence (n = 10), variable nonadherence (n = 16), moderate nonadherence (n = 40), and high adherence (n = 43). Two seizure probability trajectory groups were identified: high seizure (n = 28) and low seizure probability (n = 81). Participants with recognizable syndromes were less likely to be a member of the high seizure probability group (b = −2.372; odds ratio [OR] = 0.093; 95% confidence interval [CI](OR) = 0.015, 0.595); those with the presence of epileptiform discharges on EEG were more likely to be in the high seizure probability group (b = 1.649; OR = 5.203; 95% CI(OR) = 1.422, 19.037). Adherence trajectory group status was a significant predictor of seizure trajectory group status (partial max-rescaled R(2) = 0.13). CONCLUSIONS: Adherence trajectories and 2 biological epilepsy-specific variables explain a similar proportion of the variability in longitudinal seizure outcomes. The relationship between AED nonadherence and seizure outcomes is not linear. Early adherence interventions could change the course of seizure outcomes, particularly if variability in adherence was minimized postdiagnosis.